2017
DOI: 10.1038/srep41090
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically enhanced selective intracellular uptake of anticancer drug carrier comprising folic acid-conjugated hydrogels containing magnetite nanoparticles

Abstract: Targeted drug delivery has long been extensively researched since drug delivery and release at the diseased site with minimum dosage realizes the effective therapy without adverse side effects. In this work, to achieve enhanced intracellular uptake of anticancer drug carriers for efficient chemo-therapy, we have designed targeted multifunctional anticancer drug carrier hydrogels. Temperature-responsive poly(N-isopropylacrylamide) (PNIPAm) hydrogel core containing superparamagnetic magnetite nanoparticles (MNP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…OPloaded folate coupled SLNs exhibited significantly higher cytotoxicity as compared to plain drug solution. This phenomenon may be attributed to the conjugation of SLN with FA, which enhanced cellular uptake, via receptor mediated internalization by the cells [34]. The folate conjugation on SLNs periphery might have contributed to lower IC 50 value.…”
Section: Anticancer Potentialmentioning
confidence: 99%
“…OPloaded folate coupled SLNs exhibited significantly higher cytotoxicity as compared to plain drug solution. This phenomenon may be attributed to the conjugation of SLN with FA, which enhanced cellular uptake, via receptor mediated internalization by the cells [34]. The folate conjugation on SLNs periphery might have contributed to lower IC 50 value.…”
Section: Anticancer Potentialmentioning
confidence: 99%
“…FA was selected as the targeting ligand since it is one of the bestcharacterized ligands to be exploited for targeting cancer cells. 19 Many drug delivery vehicles, such as liposomes, proteins, polymeric NPs, linear polymers, and dendrimers, have been modified with FA to increase their cellular uptake in FR-overexpressing tumor cells. [16][17][18] Epirubicin (EPI)-loaded FA-conjugated pullulan acetate (FPA/EPI) NPs and FAconjugated chitosan-coated poly(d,l-lactide-co-glycolide) NPs might have potential applications in cervical cancer therapy.…”
mentioning
confidence: 99%
“…20,21 FA was conjugated to pullulan acetate to form the conjugated ligand and thereafter the pullulan acetate nanocarrier. Chen et al 18 and Kim et al 19 revealed that enhanced intracellular uptake by HeLa cells (FR-positive) in vitro was enabled by receptor-mediated endocytosis and that FA contributed to this effect. Our previous in vitro and in vivo results 20,21 suggested that FPA/EPI NPs showed promise in treating cervical carcinoma because of its high stability, low toxicity, and slow-release pharmacokinetic characteristics.…”
mentioning
confidence: 99%
“…2c). While the spectrum of rGO-PEG did not show any absorption peak, rGO-PEG-FA showed the additional peak at 280 nm, which was distinctive in FA [63,64]. This result supported that FA molecules were grafted on rGO surface with PEG.…”
Section: Synthesis and Characterization Of Rgo-peg-fa Nanomaterialsmentioning
confidence: 54%